Amyand’s Hernia: Rare Presentation of a Common Ailment - Sanjeev Singhal; Anu Singhal; Sanjay Singh Negi; Rahul Tugnait; Pankaj Kumar Arora; Bishwanath Tiwari; Pawan Malik; Lav Gupta; Amit Bimal; Abhishek Gupta; Rahul Gupta; Pushkar Chouhan; et al. (Case Reports in Gastrointestinal Medicine)
Inguinal hernia with vermiform appendix as content is known as Amyand’s hernia. It is a rare entity but we encountered four cases within six months. A 52-year-old female had high grade fever and evidence of inflammatory pathology involving the ileocaecal region. She was initially managed conservatively and subsequently underwent exploratory laparatomy. The appendix was perforated and herniating in the inguinal canal. Appendectomy was done with herniorrhaphy without mesh placement. A 74-year-old male with bilateral inguinal hernia, of which, the right side was more symptomatic, underwent open exploration. Operative findings revealed a lipoma of the sac and a normal appearing appendix as content. Contents were reduced without appendectomy and mesh hernioplasty was performed. A 63-year-old male with an obstructed right sided hernia underwent emergency inguinal exploration which revealed edematous caecum and appendix as content without any inflammation. Contents were reduced without any resection. Herniorrhaphy was performed without mesh placement. A 66-year-old male with an uncomplicated right inguinal hernia underwent elective surgery. The sac revealed an appendix with adhesions at the neck. Contents were reduced after adhesiolysis and hernioplasty was performed with mesh placement. Emphasis is made to the rarity of disease, variation in presentation, and difference in treatment modalities depending upon the state of appendix.